Legal Protection for Heirs who Have Not Received Their Rights in Inheritance Distribution - Muhammad Alif Santosa; Wira Franciska (International Journal Labs, 2025)
Inheritance is an important aspect of civil law that aims to provide legal certainty and justice in the transfer of property to heirs. However, the practice of inheritance distribution in Indonesia often leads to conflicts due to the denial of rights, document manipulation, or unilateral control by certain heirs. This study examines legal protection for heirs who do not receive their rights by analyzing the position of heirs in Indonesia's pluralistic inheritance law system (customary, Islamic, and Civil Code), available legal protection mechanisms, and the strategic role of notaries in preventing and resolving disputes. The research method uses a normative legal approach with the analysis of primary legal materials such as the Civil Code, KHI, and UUJN, as well as secondary materials in the form of literature and court decisions. The findings indicate that aggrieved heirs have a strong legal basis to claim their rights through civil and criminal proceedings, including lawsuits to invalidate the Certificate of Inheritance, requests for redistribution, and reports of alleged document forgery. Notaries play a central role in ensuring the validity of documents, the involvement of all heirs, and the prevention of manipulative actions that harm other parties. Additionally, the low legal literacy of the public regarding inheritance rights contributes to disputes that damage family relationships. Therefore, preventive measures through legal education and transparent inheritance distribution with notary assistance are necessary. The strict enforcement of the law and the active involvement of notaries are key to achieving justice and harmony in inheritance distribution.